Entrepreneurial Challenges of Transgender Entrepreneurs in Pakistan - Sohail, Farhan; Abbas, Mehdi; Siddiqui, Arsalan Ahmed; Khan, Essa; Rehman, Asif; Ali, Sheikh Muhammad (The journal of contemporary issues in business and government, 2022)
Social marginalization has made it difficult for transgender people to integrate into regular society and to create businesses. Sporadic transgender people have prepared the ground for the business to get started. The purpose of this research is to look into the entrepreneurial hurdles that transgender entrepreneurs confront in Pakistan. The interviewees included a total of 20 transgender entrepreneurs who had quit begging and commercial sex work and founded a business across Pakistan. The grounded theory study' key findings identified seven critical areas, including competitors, discrimination, financial resources, human resources, natural disasters, product awareness, and technology issues. Participants stated that discrimination and a lack of financial resources made starting a business extremely difficult. These findings expand our understanding of cisgender entrepreneurs' obstacles beyond what we currently know.